Evaluation of the Bonding Shear Strength between Enamel and Dentin Feldspathic Porcelain and Two Different Monolithic Zirconia with Low and High Translucency - Amirhossein Fathi; Yeganeh Natanzian; Mahsa Ghorbani; Ramin Mosharraf (International Journal of Dentistry)
Introduction. The utilization of ceramics in the field of dentistry has seen a significant rise owing to their esthetic appeal and excellent functional properties. The use of ceramics in the field of dentistry has witnessed a notable surge, driven by their appealing esthetics and exceptional functional attributes. Zirconia, distinguished by its exceptional mechanical strength, plays a pivotal role in the fabrication of posterior crowns and bridges. Among zirconia variants, monolithic zirconia stands out, where the entire restoration is crafted from zirconia material. In parallel, feldspathic porcelain, chosen for its remarkable resemblance to natural tooth enamel, represents another significant ceramic type. This study aims to evaluate the shear bond strength (SBS) between two types of monolithic zirconia with two types of feldspathic porcelain. Methods and Materials. Forty-four monolithic zirconia veneered discs with feldspathic porcelain were subjected to SBS testing. The dimensions of the discs were 7 mm in diameter and 5 mm in height (3 mm of zirconia and 2 mm of porcelain). Subsequently, the specimens were subjected to a universal testing machine at a speed of 0.5 mm/min until failure occurred. The type of failure was examined using scanning electron microscopy. One-way analysis of variance (ANOVA), two-way ANOVA, Fisher’s test, and multiple Tukey comparisons were used as statistical analyses. Results. The highest SBS was achieved by the high-translucency monolithic zirconia with enamel porcelain group (18.81 ± 3.18 MPa) and the high-translucency monolithic zirconia with dentin porcelain group (17.89 ± 2.75 MPa), followed by the low-translucency monolithic zirconia with dentin porcelain group (15.04 ± 2.24 MPa) and the low-translucency monolithic zirconia with enamel porcelain group (14.33 ± 2.00 MPa), respectively. Additionally, the most common type of failure pattern observed was mixed, followed by adhesive failure. Conclusion. The translucency of the porcelain did not significantly affect SBS, while the type of monolithic zirconia used had a significant impact. Furthermore, there was no discernible relationship between the four groups in terms of the distribution of failure patterns.